Teachers’ Teaching Strategies For Teaching Speaking Skills At Junior High School - Nurul Octavia; Yuli Astutik; Endang Mastuti Rahayu (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
A teaching strategy is defined as a set of activities carried out to achieve a learning goal. This study aims to analyse the strategies implemented by the teacher for eighth grade students at one of Junior High School in Pasuruan, East Java. Furthermore, this study looks into the teacher's motivations for using the strategies in teaching speaking skills. This research used qualitative research with a case study design. The instruments used in this research were observations and interviews. The results of this research show that the teachers implemented the teaching strategies proposed by Thornbury. Moreover, the teacher was known for applying other strategies such as reading aloud, repetition drills, and modelling cooperative learning as they aligned with the students’ competencies. These research findings indicate that the teacher successfully implemented her strategies in teaching speaking skills, which can be proven from the students’ responses that they are motivated to learn English, especially speaking skills.